Poverty, Land Degradation and Climatic Uncertainty - Sverre Grepperud (Statistics Norway, Research Department, 1996)
This paper studies the implications of climatic uncertainty and poverty for resource degradation. In doing so, two partial models are considered. The first model focuses on productive inputs only, while the second model describes the role of soil conservation inputs. Both models are first analysed under farmer risk aversion. Then farmers which operate at a minimum level of subsistence are considered. It is shown that the consequences for the soil conservation decision from both risk aversion and poverty tend to be opposite for the two models. Output-induced soil depletion increases when agrarian producers are poor and risk averse. The incentives for soil conservation improve for the same two reasons when soil conservation inputs are analysed.
Keywords: Q12; Q20; 330; Farm households; soil fertility; risk preferences.